Nomenclatural status of Euptychia mollina Hübner, 1818 (Lepidoptera: Nymphalidae: Satyrinae) - Lamas, Gerardo; Nakahara, Shinichi (Zootaxa, 2015)
The purpose of this note is to clarify the nomenclatural status of Euptychia mollina Hübner, 1818, the type species of Euptychia Hübner, 1818, as there seems to be confusion regarding its year of publication. Due to an unfortunate oversight, Lamas (2004) listed the name as Euptychia mollina (Hübner, [1813]), and this mistake has been repeated in the subsequent literature (e.g. Brévignon 2005; Warren et al. 2014; Neild et al. 2014).